Screening on the factor affecting the alkaline pretreatment of fiber pressed oil palm frond - Nur Fatin Nadiah, Fauzi (2015)
Oil palm fronds are a by-product from the harvest of the fresh fruit from oil palms. Nowadays, oil palm fronds are used as a source of roughage for ruminants. Oil palm fronds have lignocelluloses biomass is an organic residue which consists of mainly cellulose, lignin and hemicelluloses, whose basic units are sugars that can be fermented into sugar or other chemicals. The main objective of this research is to screening the factor that affect the alkaline pretreatment in lignin removal. This research was conducted based on two-level factorial design with a total sixteen runs. The studied variables or factors (parameters) e.g. sodium hydroxide concentration, temperature, time pretreatment, lime concentration and ultrasonication were denoted by high level (+1) and low level (-1) where their actual code are 0.50-10%, 40-90ºC, 15-120 minutes, 2.00-10.00% and yes or no, respectively. The oil palm frond biomass with less than 1.0mm were first pre-soaked in mixture of sodium hydroxide and lime solution that have different concentration, then incubated in an microwave with desired temperature and time. For the alkaline-assisted ultrasonic, the same method is approach but by using ultrasonic probe. The OPF was then filtered and washed thoroughly with de-ionized water and dried in oven for 24 hour. Then, the filtrate was weighed. The analysis done using Two-Level Factorial by Design Expert software shows that three factors are affecting with high contribution towards the lignin removal. These factors are the sodium hydroxide concentration, temperature and lime concentration. The factors of NaOH concentration, temperature and lime concentration contributed with 76.30%, 0.50% and 0.29% respectively to the delignification process. In addition, the data obtained was fitted into response which is the amount of lignin removed, YL for statistical analysis. Lignin response was found to be significant in terms of model (F-value = 39.79), the regression coefficient, R2 = 0.9876 and adjusted regression coefficient RA2 = 0.9628.